Book Review: B.V.R. Subbu, Santro: The Car that Built a Company. Issue 1 (February 2019) - Tandon, Neelam
B.V.R. Subbu, Santro: The Car that Built a Company . Gurugram: Hachette Book Publishing India, 2017, 254 pp., ₹599. ISBN: 978-93-5195-208-4 (Hardback).